The Role of Student Self-Assessment in IAKN Ambon: Promoting Need-Supportive Christian Educational Practices - Novita Loma Sahertian; Benjamin Metekohy; Noni Matital; Tobias Dominggus Sohilait (Jurnal Pendidikan Agama Kristen (JUPAK), 2025)
Promoting sustained academic engagement among university students remains a persistent and complex challenge. Alarmingly, many higher education institutions continue to report low levels of student involvement, particularly in areas requiring integration competence and awareness of equality issues. In response to this phenomenon, the present study explores student self-assessment (SSA) as a pedagogical instrument to strengthen the connection between need-supportive teaching and desired learning outcomes. Specifically, the study proposes the incorporation of SSA into routine teaching evaluation practices as a means to enhance student understanding, foster autonomy, and promote inclusive learning environments. The primary objective of this study research was to examine the impact of SSA on students’ academic performance within the context of a "Christian Education" (PAK). To achieve this, a one-group pre-post experimental design was employed, complemented by correlational analysis to assess the relationship between SSA practices and academic achievement. Data were collected using a series of standardized academic tests and an adapted SSA questionnaire designed to measure students' perceptions and engagement in the self-assessment process. The findings reveal that regular engagement in self-assessment significantly mediates the relationship between externally managed instruction and students’ independent academic achievement. Notably, the integration of SSA was associated with enhanced student engagement and improved academic performance, even after controlling for potential confounding variables. These results suggest that SSA not only functions as a reflective practice but also serves as a behavioural mechanism through which need-supportive teaching exerts its influence on student outcomes. Overall, this study contributes to the growing body of literature on learner-centered pedagogy by demonstrating the empirical value of SSA in fostering student autonomy, engagement, and performance. The implications underscore the importance of embedding SSA into institutional teaching evaluations and highlight avenues for future research on its long-term effects across various disciplines.